Academic Monitoring Information System Using Task Centered System Design Method Based On Web - Haliza, Nur; Suendri, Suendri (Research Group of Data Engineering, Faculty of Informatics, 2025)
Manual academic monitoring systems at SMA Swasta Teladan Cinta Damai present several challenges, such as delayed information delivery, data entry errors, and lack of transparency in academic records. This study aims to design and develop a web-based Academic Monitoring Information System using the Task Centered System Design (TCSD) approach, which focuses on the actual needs and tasks of users such as teachers, students, and parents. The system is developed using PHP as the programming language and MySQL as the database, and follows the Waterfall development model, which includes stages such as requirements analysis, system design, implementation, and testing. The results show that the system can present academic information in real time, improve monitoring efficiency, and facilitate access to information for all stakeholders. With its intuitive interface and task-oriented features, this system provides a digital solution that enhances the quality of academic management in the school environment.